북한의 농업개발을 위한 남북한 협력 전략 - 권태진 (한국농촌경제연구원, 2012)
This paper aims to suggest a strategy of inter-Korean cooperation for the development of North Korean agriculture. In the first part, the current agricultural situation and issues will be described. North Koreans have suffered from the chronic food deficit. North Korean government has tried various policies to solve food problems. However, the current state is not much different from the previous situation. North Korea's new leader Kim Jong-un has set solving food problem as the first priority. He is expected to reform the agricultural system gradually. Therefore, strategies on how to cooperate with North Korea to develop its agriculture should be prepared. During the process, the experience of international society on agricultural development assistance to North Korea will give us lessons. The most important thing when trying to achieve sustainable and effective agricultural development cooperation is to set explicit goals and directions. Transparent process is especially important between two Koreas. Proceeding step by step, in accordance with the improvement of relationship between the South and the North, will enhance the effectiveness.
Keywords: 북한; 농업; 개발협력; North Korea; agriculture; development cooperation